2017
DOI: 10.1016/j.actatropica.2015.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Effect of repeated mass drug administration with praziquantel and track and treat of taeniosis cases on the prevalence of taeniosis in Taenia solium endemic rural communities of Tanzania

Abstract: This study evaluated the effect of mass drug administration (MDA) with praziquantel administered to school-aged children (SAC) combined with 'track and treat' of taeniosis cases in the general population on the copro-antigen (Ag) prevalence of taeniosis. The study was conducted in 14 villages in Mbozi and Mbeya district, Tanzania. SAC made up 34% of the population and received MDA with praziquantel (40mg/kg) in 2012 (both districts) and in 2013 (Mbozi only). Three cross-sectional population-based surveys were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 19 publications
1
39
0
Order By: Relevance
“…However, the presence of taeniosis-Ab only reflects exposure to the adult tapeworm and cannot differentiate past from present infections. Previous estimates of the prevalence of adult tapeworm infections measured with a copro-Ag-ELISA in endemic areas vary from 0.1 to 4.0% in community-based settings, with only one study from Zambia reporting a prevalence of 11.9% [13, 1518]. In our study, all individuals with a positive taeniosis-Ab titer lived in the Mbulu district (Fig.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…However, the presence of taeniosis-Ab only reflects exposure to the adult tapeworm and cannot differentiate past from present infections. Previous estimates of the prevalence of adult tapeworm infections measured with a copro-Ag-ELISA in endemic areas vary from 0.1 to 4.0% in community-based settings, with only one study from Zambia reporting a prevalence of 11.9% [13, 1518]. In our study, all individuals with a positive taeniosis-Ab titer lived in the Mbulu district (Fig.…”
Section: Discussionmentioning
confidence: 55%
“…Cross-sectional studies conducted in rural communities have reported prevalence proportions of taeniosis using a copro-antigen-enzyme linked immunosorbent assay (copro-Ag-ELISA) of 19.9% in western Kenya, 6.3 to 11.9% in the Eastern Province of Zambia, and 1.1 to 5. 2% in Tanzania [14–18]. Moreover, a Tanzanian study conducted in Mbeya Rural District reported a taeniosis-antibody (Ab) prevalence of 4.1% using a rES38-immunoblot [17].…”
Section: Introductionmentioning
confidence: 99%
“…So far no intervention programmes or studies have tried this modality in Africa and therefore comparison to African field data is impossible. Only one study from Africa, where Braae et al [15] measured the effect of MDA of praziquantel given to Tanzanian school-aged children for schistosomiasis treatment in combination with 'track-and-treat' of taeniosis cases diagnosed during the study, have shown an effect on taeniosis prevalence. Garcia et al [23] conducted a short-term intervention study in Peru targeting both hosts and measured the outcome based on EITB on pigs only.…”
Section: Discussionmentioning
confidence: 99%
“…Initial infection for humans and pigs were set according to district baseline data from Braae et al [15] and Braae et al [38], respectively, and initial infection intensity proportions in pigs were based on data from the same area by comparing lingual examination and Ag-ELISA results [4]. Positives for lingual examination were considered high intensity infections, and Ag-ELISA positives considered low intensity infection if not concurrently positive by lingual examination.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation